2007
DOI: 10.1242/dev.008441
|View full text |Cite
|
Sign up to set email alerts
|

HIF1α regulation ofSox9is necessary to maintain differentiation of hypoxic prechondrogenic cells during early skeletogenesis

Abstract: During early stages of limb development, the vasculature is subjected to extensive remodeling that leaves the prechondrogenic condensation avascular and, as we demonstrate hereafter, hypoxic. Numerous studies on a variety of cell types have reported that hypoxia has an inhibitory effect on cell differentiation. In order to investigate the mechanism that supports chondrocyte differentiation under hypoxic conditions, we inactivated the transcription factor hypoxia-inducible factor 1␣ (HIF1␣) in mouse limb bud me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

14
257
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 267 publications
(275 citation statements)
references
References 54 publications
14
257
2
Order By: Relevance
“…46,47 Conditional knockout of HIF-1α in the limb bud mesenchyme of mice indicated that HIF-1α expression is probably not required for the initiation of mesenchyme condensation. 46,47 However, HIF-1α is critically involved in the timely differentiation of the mesenchymal cells into chondrocytes, via mechanisms that are still largely unknown, although regulation of SOX-9 (a principal transcription factor involved in chondrogenesis) might be involved. 48,46 In addition, lack of HIF-1α delays the terminal differentiation of chondrocytes, which is probably a downstream effect of delays in the initiation of chondrogenesis.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…46,47 Conditional knockout of HIF-1α in the limb bud mesenchyme of mice indicated that HIF-1α expression is probably not required for the initiation of mesenchyme condensation. 46,47 However, HIF-1α is critically involved in the timely differentiation of the mesenchymal cells into chondrocytes, via mechanisms that are still largely unknown, although regulation of SOX-9 (a principal transcription factor involved in chondrogenesis) might be involved. 48,46 In addition, lack of HIF-1α delays the terminal differentiation of chondrocytes, which is probably a downstream effect of delays in the initiation of chondrogenesis.…”
mentioning
confidence: 99%
“…46,47 However, HIF-1α is critically involved in the timely differentiation of the mesenchymal cells into chondrocytes, via mechanisms that are still largely unknown, although regulation of SOX-9 (a principal transcription factor involved in chondrogenesis) might be involved. 48,46 In addition, lack of HIF-1α delays the terminal differentiation of chondrocytes, which is probably a downstream effect of delays in the initiation of chondrogenesis. 46,47 Notably, conditional HIF-1α -knockout mice also showed a striking impairment of joint development, 46,47 a defect that could also be related to SOX-9 because (at least in vitro) hypoxia increases matrix accumulation by chondrocytes of the articular surface, in a manner dependent on this transcription factor.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Here, we show nerve innervation patterns throughout limb outgrowth. Similarly, cartilage and bone analysis is usually assessed in mouse limb studies at specific time points to study specific gene function and action (for example, Amarilio et al, 2007; Collinson et al, 2018; Firulli et al, 2005; Nowlan et al, 2010; Ray et al, 2015; Tavella et al, 2004). Here, we show in detail the progression of cartilage and bone development throughout fore‐ and hindlimb patterning.…”
Section: Introductionmentioning
confidence: 99%